O porquê da possibilidade da regulamentação do lobby no Brasil - Oliveira, Rogério Donizetti Campos de (2015)
This monographic research is an exhibition of why the possibility of regulation of lobby in Brazil. With inserted lobby in the United States sought to trace here the way of regulation of the activity in Brazil highlighting the peculiarities of the political system to serve as a support for new legislation. In comparative law, Argentina, Chile, Mexico and Peru, has its particular scope to check the usefulness of some institutes the Brazilian legal system. In short, the lobby would act as a device or technique to solve the confusing web of greed because of the acceleration and quality of knowledge facilitated by this in order to ensure optimal management of resources proposed in the administration of the state and its policies. The foregoing teaching takes care of the analysis of a particular institute in a legal system to prove its plausible use in another system, since reconciled to the reality and the mobilized society to influence the government by which she was elected as a representative, for their rights, It is the lobby of these representations